Design and experiment of air-suction drum-type seedling seeder for irregular-shaped vegetable seeds - Yanjun Li; Yunqiang Liu; Yichao Ning; Hongxin Wu; Yaqian Zhao (Scientific Reports)
Abstract In order to meet the requirements of hole tray seedling transplanting operation for tomato, pepper and other irregular-shaped vegetable seeds, and to solve the problems of poor seeding performance of irregular-shaped vegetable seeder, this study designed an Air-suction Drum-type Precision Seeder. The basic structure and working principle of the seeder were elaborated, the key components were designed, and the distribution of the airflow field in the flow paths of the suction nozzles of three different hole types was simulated and analyzed by Fluent software; the relationship between the main influencing factors of the seeder’s operational performance (suction air pressure, clearing air pressure, and vibration frequency of the seed cassette) and the sowing indexes (replanting rate, cavity rate, and qualification rate) was investigated and the relationship between the factors and the sowing indexes (reseeding rate, cavity rate, and qualification rate) was analyzed by the quadratic orthogonal combination experiment method. The relationship between the main factors (suction air pressure, clearing air pressure and vibration frequency of seed supply box) and the seeding indexes (reseeding rate, empty hole rate and pass rate) was studied, and the effects of the factors and their interactions on the indexes were analyzed and the parameters were optimized by multi-objective optimization method. The results show that: the factors affecting the seeding qualification rate in the order of suction air pressure, clearing air pressure and vibration frequency, the optimal parameter combination of suction air pressure 16.0 kPa, clearing air pressure 3.4 kPa, vibration frequency of 50 Hz, in the optimal parameter combination of the sowing test, to get the replanting rate, the rate of empty holes, the qualification rate of the time were 1.4%, 1.7% and 96.9%, respectively.It shows that the performance of this seeder is better adapted, accurate and efficient, and can meet the requirements of irregular-shaped vegetable seeding operation. The results of the study can provide a reference for the research and development of the irregular-shaped vegetable seedling seeding machine.